(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study presents a DSc-level theoretical and empirical analysis of the 4K Model of Teaching—Critical Thinking, Creativity, Communication, and Collaboration—as an integrated pedagogical framework for developing 21st-century competencies in contemporary educational systems. The research examines the conceptual foundations of the 4K model within constructivist learning theory, cognitive psychology, and competency-based education paradigms, and evaluates its structural components through analytical modeling and pedagogical system analysis. The study investigates instructional design strategies, assessment alignment mechanisms, and classroom interaction dynamics that support the systematic implementation of 4K competencies across disciplines. Through a synthesis of theoretical frameworks and applied educational modeling, the research establishes measurable performance indicators and proposes an integrative instructional architecture that enhances learner autonomy, problem-solving capacity, and socio-cognitive development. The findings contribute to the modernization of teaching methodologies and provide a scientifically grounded model for sustainable educational transformation in higher and general education contexts.